Políticas de rotación de personal de Comercial Anthony - en la ciudad de Babahoyo - Garcia Anzules, Joselyn Yomira (2021)
This study was carried out at Market Anthony with the purpose of analyzing the levels of staff turnover that the company currently maintains, and identifying the causes and effects that can damage the institutional image and decrease the operational efficiency of the commercial. This case study was based on fulfilling the criteria of the descriptive research and the quantitative method, to generate an exhaustive analysis on the numerical data referring to the number of employees hired and the number of dismissed or who no longer have employment relationships with the company in study. The results obtained from the research related to the management of human talent at Market Anthony are the following: motivational plans are not handled, the level of staff turnover exceeds more than 15% on average, the payment of overtime hours is not considered. Work and more than half of the employee payroll does not enjoy Social Security benefits. The Anthony Company does not handle written employment contracts, but only verbal contracts. The inadequate work environment, the few opportunities for promotion, and the flight of staff due to job dissatisfaction are the main factors for producing high levels of staff turnover in a company.